Fluoride and dental health - Iba, Bemhemba; Falegbe, Rapheal Kehinde; Iortyom, Chile; Nwaohabuenyi, Thelma Ebere; Asa, Yomi Isaac; Ibeobi, Ada Cynthia; Dogoh, Aondover F. (Orapuh Journal, 2021)
Fluoride plays an important role in the prevention of dental caries. Dental caries has remained a global public health concern and is responsible for the highest cause of patient visits to the dental clinic. To review fluoride and dental health, an electronic search of scientific literature was conducted. Database searches were carried out using the terms: “fluoride and oral health”, “sources of fluoride”, “water fluoridation”, “fluoride application”, “adverse effects of fluoride”, and “functions of fluoride in dental health”. There were several works of the literature identified to be related to the subject but only 50 met the inclusion criteria of being published from 2017 to 2021 and they were subsequently reviewed. 32 of the literature reviewed were selected from peer-reviewed journals, 6 from corporate organizations and 12 were articles assessed via Google Scholar. The review observed that fluoride was effective in the control of dental caries and by extension improvement of dental health. However, excessive ingestion of fluoride was responsible for certain side effects, chiefly, dental fluorosis. Therefore, fluoride when delivered appropriately is safe and an effective means of curbing dental caries without any corresponding side effects.